(untitled) (World Bulletin of Social Sciences, 2022)
The author raises the problem of relations between the subjects of the pedagogical process. Four main blocks of consideration of the topic are identified and analyzed: the conflict "teacher-student", "teacher-parent", "teacher-administration", "teacher-teacher"